Research progress on pleiotropic neuroprotective drugs for traumatic brain injury - Zhao, Qinghui; Li, Huige; Li, Hongru; Zhang, Jianhua (Frontiers in Pharmacology, 2023)
Traumatic brain injury (TBI) has become one of the most important causes of death and disability worldwide. A series of neuroinflammatory responses induced after TBI are key factors for persistent neuronal damage, but at the same time, such inflammatory responses can also promote debris removal and tissue repair after TBI. The concept of pleiotropic neuroprotection delves beyond the single-target treatment approach, considering the multifaceted impacts following TBI. This notion embarks deeper into the research-oriented treatment paradigm, focusing on multi-target interventions that inhibit post-TBI neuroinflammation with enhanced therapeutic efficacy. With an enriched comprehension of TBI's physiological mechanisms, this review dissects the advancements in developing pleiotropic neuroprotective pharmaceuticals to mitigate TBI. The aim is to provide insights that may contribute to the early clinical management of the condition.